セールロンダーネ サンチ チイキ セッピョウ チョウサ タイ ホウコク 1989-1990 (JARE-31) - 本山, 秀明; モトヤマ, ヒデアキ; 東, 信彦; アズマ, ノブヒコ; Decleir, Hugo; Huybrechts, Philippe; Motoyama, Hideaki; Azuma, Nobuhiko (1990)
P(論文) 第31次南極観測隊(夏隊)の雪氷調査隊4名(第31次観測隊員, 第30次観測隊員, 交換科学者2名)は, 12月後半に「ACR計画」の一環の観測としてLルート沿いの無人気象観測装置のデータ回収, 電池交換を行った後, 1月2日-28日にセールロンダーネ山地 (Sφr Rondane Mountains)でドリルテスト, 雪氷調査を行った。液封型深層メカニカルドリルのプロトタイプでの掘削テストをジェニングス氷河(Jenningsbreen)の中流部の裸氷帯で実施し, 良好な結果を得た。交換科学者はこの氷河で流動と質量収支のための雪尺の設置と測量を行い, 第32次観測隊で再測する予定である。また, ブラットニーパネ(Brattnipene)・グーセン氷河(Goosenbreen)での雪尺網の再測から, 例年に比べてこの1年の積雪が多いことが分かった。今回セールロンダーネ山地調査隊のためにヘリコプターが2機導入され, これを利用し, セールロンダーネ南部のナンセン氷原(Nansenisen)の火山灰層を含む表面氷の採取を行った。 Summer party of the 31st Japanese Antarctic Research Expedition (JARE-31) carried out maintenance of automatic meteorological stations, glaciological observation, and drilling test for "Antarctic Climate Research (ACR)" Project from late December 1989 to January 1990 around the Sør Rondane Mountains region. This party is constituted by four glaciologists including two Belgian observers and one JARE-30 member. Three prototypes of electromechanical ice drill for deep core sampling using untifreezing liquid were successfully tested on a bare glacier at Jenningsbreen (Jennings glacier). On the same glacier, dynamics of glacier movement were studied by Belgian observers. Mass balance measurement was conducted on Goosen-breen (Goosen glacier) of Brattnipene. Two helicopters were employed for geological and topographical survey in the Sør Rondane region, so that we were able to fly to Nansenisen, south of Sør Rondane, and to obtain surface bare ice within dust band (volcanic ash?). departmental bulletin paper